PENINGKATAN HASIL BELAJAR IPS TEMA PERISTIWA DALAM KEHIDUPAN MENGGUNAKAN METODE PEMBELAJARAN SCRAMBLE PADA SISWA KELAS V UPT. SD NEGERI 20 BARINGIN - Sri Gustina (Ensiklopedia of Journal, 2021)
This study aims to determine the increase in social studies learning outcomes the theme of events in life using the scramble learning method for class students V UPT. SD Negeri 20 Baringin sub-district Lima kaum. This type of research is classroom action research (PTK). The PTK design used Kemmis and Taggart which included planning, action and observation, and reflection. Data collection techniques using tests. The data analysis technique uses descriptive analysis to analyze student learning outcomes. The research subjects were class students V UPT.SD Negeri 20 Baringin which amounted to 20 students. The criterion for success is at least 85% of the total number of students achieving the Minimum Completion Criteria (KKM) that the school has set, namely the value of 80. The results show that there is an increase in social studies learning outcomes Themes of Events in Class Student V UPT. SD Negeri 20 Baringin by using the scramble learning method. This can be seen from the increase in students' social studies learning outcomes (Themes of Events in Life) from pre-action, cycle I, and cycle II. In the pre-action, the students 'learning completeness was obtained by 50%, the first cycle was 72.22%, and in the second cycle, the students' learning completeness was obtained by 86.11%. The increase in student learning outcomes from pre-action to cycle I was 22.22% and from cycle I to cycle II was 13.89%. While the average value in pre-action was 66.67 to 77.5 in cycle I and to 82.5 in cycle II So, the scramble learning method can improve the social studies learning outcomes of class V students UPT. SD Negeri 20 Baringin.